Directory of women experts in Asia and the Pacific. (United Nations, Economic and Social Commission for Asia and the Pacific, 1993)
A response to an increasing demand among Economic and Social Commission for Asia and the Pacific (ESCAP) members and associate member governments, non-government organizations, private sectors and experts for a regional database on women experts. The database includes a very limited 639 experts from 20 countries in the Asia and Pacific region. The directory presents a profile of each expert giving information on their present position, work experience, educational background, publications, professional associations, language, and nationality, areas of expertise, contact numbers and address. The directory also features an index of areas of expertise and of country /area index.